Power conversion efficiency in thin film solar cell: A review - Ho, Soon Min (Trade Science Inc, 2016)
This review paper describes the preparation of thin films using various deposition methods such as vacuum based method and solution based deposition technique. The obtained thin films could be applied in solar cell due to many advantages including direct band gap between 1-2 eV and high absorption coefficient value. In this work, the construction and performance behaviors of solar cell were fabricated and discussed.